Kinetics of dendrite growth and dendritic fragmentation in the undercooled Co81.2 Cu18.8 alloy's melt. Issue 5 (14th May 2014) - Galenko, P.K.; Kolbe, M.; Herlach, D.M.; Rettenmayr, M.
Abstract : The growth velocity during solidification of an undercooled melt of a Co-Cu alloy processed by electromagnetic levitation was measured using a high speed video camera. Applying a model of local non-equilibrium solidification, theoretical predictions of dendrite growth velocity and dendritic growth radii are compared with high-accuracy measurements of the growth kinetics. As the undercooling ΔT reaches a critical value consistent with the dendrite growth velocity being equal to the atomic diffusion speed V D in bulk liquid, ΔT = ΔT ( V D ), the velocity-undercooling relationship exhibits a break-point. A distinct change in the dendritic growth mechanism exists with the onset of complete solute trapping and chemically partitionless solidification of the core of the main stems of the dendrites occurs. A complete transition to the thermally controlled growth of dendrites occurs at ΔT = ΔT ( V D ) that leads to essential changes in the microstructure of dendritic patterns The phenomenon of dendritic fragmentation in Co-Cu melts, solidifying at ΔT < ΔT ( V D ), is discussed.